Application of the Problem Based Learning Model in Increasing Student Activity and Learning Outcomes in Beautiful Materials Mutual Respect - Muhammad Abdul Nafi' (Research Journal on Teacher Professional Development, 2025)
This research aims to increase the activeness and learning outcomes of grade V students in the material "The Beauty of Mutual Respect" at SD Negeri Srondol Wetan 04 Semarang City for the 2024/2025 Academic Year through the application of the Problem Based Learning (PBL) learning model. This research is a Class Action Research (PTK) which is carried out in two cycles, namely cycle 1 and cycle 2. Each cycle consists of planning, implementation, observation, and reflection stages. Data was collected through observation, learning outcome tests, and documentation. The results of the study show that the implementation of PBL is able to significantly increase student activity and learning outcomes. Student activity increased from an average score of 40 in the first cycle to 70 in the second cycle. Similarly, student learning outcomes showed an increase with the average score rising from 55 in cycle I to 80 in cycle II. The implementation of PBL has a positive impact on students' motivation, active participation, and critical thinking skills. Thus, the PBL learning model can be implemented as an alternative effective learning strategy to improve the quality of learning in elementary schools.